2-Phenylbenzofuran derivatives as butyrylcholinesterase inhibitors: Synthesis, biological activity and molecular modeling. Issue 9 (1st May 2016) - Delogu, Giovanna L.; Matos, Maria J.; Fanti, Maura; Era, Benedetta; Medda, Rosaria; Pieroni, Enrico; Fais, Antonella; Kumar, Amit; Pintus, Francesca
Graphical abstract: Abstract: A series of 2-phenylbenzofurans compounds was designed, synthesized and evaluated as cholinesterase inhibitors. The biological assay experiments showed that most of the compounds displayed a clearly selective inhibition for butyrylcholinesterase (BChE), while a weak or no effect towards acetylcholinesterase (AChE) was detected. Among these benzofuran derivatives, compound16 exhibited the highest BChE inhibition with an IC50 value of 30.3 μM. This compound was found to be a mixed-type inhibitor as determined by kinetic analysis. Moreover, molecular dynamics simulations revealed that compound16 binds to both the catalytic anionic site (CAS) and peripheral anionic site (PAS) of BChE and it displayed the best interaction energy value, in agreement with our experimental data.